1990
DOI: 10.1002/mc.2940030609
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ionizing radiation on expression of genes encoding cytoskeletal elements: Kinetics and dose effects

Abstract: We examined the modulation in expression of genes encoding three cytoskeletal elements (beta-actin, gamma-actin, and alpha-tubulin) in Syrian hamster embryo (SHE) cells following exposure to ionizing radiations. Early-passage SHE cells were irradiated in plateau phase with various low doses (12-200 cGy) of neutrons, gamma-rays, or x-rays. RNA samples were prepared from cells at different times postexposure and were analyzed for levels of specific transcripts by northern blots. The results revealed that alpha-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
23
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 19 publications
2
23
0
Order By: Relevance
“…43 On the other hand, a-tubulin, g-actin and interleukin 1 were similarly induced both by g-rays and neutrons. 44,45 In the present study, both neutron and photon irradiation activated CArGregulated gene expression (Figs 1 and 2). However, the higher cytotoxic efficacy of neutrons was not reflected in Activation of CArG promoters for gene therapy O Greco et al stronger promoter activation.…”
Section: Discussionsupporting
confidence: 58%
“…43 On the other hand, a-tubulin, g-actin and interleukin 1 were similarly induced both by g-rays and neutrons. 44,45 In the present study, both neutron and photon irradiation activated CArGregulated gene expression (Figs 1 and 2). However, the higher cytotoxic efficacy of neutrons was not reflected in Activation of CArG promoters for gene therapy O Greco et al stronger promoter activation.…”
Section: Discussionsupporting
confidence: 58%
“…These regulons are rapidly and readily induced and control a series of genes, including those encoding for AOEs (14). This biological principle was also found to be relevant in the mammalian system (15)(16)(17)(18)(19)(20)(21)(22). Most studies of higher organisms examined the AOE response hours and days after irradiation and are, therefore, confounded by influences, such as inflammation, secondary to radiation per se.…”
mentioning
confidence: 94%
“…Most studies of higher organisms examined the AOE response hours and days after irradiation and are, therefore, confounded by influences, such as inflammation, secondary to radiation per se. No study on early events of AOE transcription has been reported to date, to our knowledge, although it is known that as soon as 30 min after ionizing irradiation SOD activity can be significantly elevated (18). When they approached this problem, de Toledo and coworkers (7) showed by in vitro studies that mRNA levels for Cu-Zn SOD and CAT in fibroblasts were not increased 1-6 hr after ionizing irradiation at low (3.6 Gy) or high (20 Gy) doses.…”
mentioning
confidence: 95%
“…Since we and others have found that ionizing radiation increases PKC activity (11)(12)(13) and PKC has been shown to regulate K+ channels in excitable cells (14), we sought to determine whether channel activity was dependent on PKC activation. After chronically exposing A549 cells to phorbol esters before radiation, PKC activity was measured and found to be downregulated to 10o of untreated controls.…”
mentioning
confidence: 99%